Conceptual design of a hybrid airship - Marques, António José Nunes (2014)
Nowadays freight transportation is facing an increased concern about the environment pollution, infrastructures congestion and different measures are being implemented to try to make it more efficient and economical. Because of that there is an increasing interest in airship technology and so new advances are being made in this type of transportation. Such as the Hybrid Airship that is overcoming the previous airships. These new technologies are paving the way for a new future in airships and freight transportation. This work aims to demonstrate the technology of this type of transportation mode and some of its new advances. The fields of materials and structures, stability and control, propulsion system and the certification and legislation for an airship design are described. Also, a conceptual design of a Hybrid Airship for the mission of freight transportation will be made and the airship behavior is also briefly described. To complement the work, the development of a prototype to test the theory proposed is presented.